Synthesis of Novel Octahedral Silicon Compounds; Synthesis of Bis[3-(1-{[aryl(hydroxy)methylene]hydrazinylidene}ethyl)-6-methyl-2-oxo-2H-pyran-4-olato-N,O,O′]silicon(IV) - Karamouzi, Sotiria; Maniadaki, Anna; Nasiopoulou, Despina A.; Kotali, Elvira; Kotali, Antigoni; Harris, Philip A.; Raftery, James; Joule, John A. (Synthesis, 2013)
The synthesis of new silicon compounds is reported via the cyclization of dehydroacetic acid N-acylhydrazones with silicon tetraacetate. The procedure involves formation of new octahedral hexacoordinated silicon structures.
Keywords: octahedral silicon; dehydroacetic acid; N-acylhydrazones; silicon tetraacetate; hypervalent silicon